The fate of traditional schools in a context of educational modernization: the case of Si-shu in China. Issue 1 (27th November 2020) - Jiang, Chunjiao; Mao, Pengcheng
Abstract : Purpose: The purpose of this paper is to examine how Si-shu, a traditional form of local, private education grounded in classical instruction, responded to the rapid modernization of education during the late Qing dynasty and early Republic of China and to explain why these schools, once extraordinarily adaptable, finally disappeared. Design/methodology/approach: The authors have examined both primary and secondary sources, including government reports, education yearbooks, professional annals, public archives, and published research to analyze the social, political and institutional changes that reshaped Si-shu in the context of China's late-19th- and early-20th-century educational modernization. Findings: Si-shu went through four stages of institutional change during the last century. First, they faced increased competition from new-style (westernized) schools during the late Qing dynasty. Second, they engaged in a process of intense self-reform, particularly after the Xinhai Revolution of 1911. Third, they were marginalized by the new educational systems of the Republic of China, especially the Renxu School System of 1922 and the Wuchen School System of 1928. Finally, after the foundation of the People's Republic of China in 1949, they were considered remnants of feudal culture and forcibly replaced by modern schools. Originality/value: This paper brings hitherto unexplored Chinese sources to an English-speaking audience in an effort to shed new light on the history of traditional Chinese education. The fate of Si-shu was part of the larger modernization of Chinese education – a development that had both advantages and disadvantages.